A comprehensive design and rating study of evaporative coolers and condensers. Part I. Performance evaluation - QURESHI, BILAL AHMED (2020)
Abstract The mathematical models of evaporative fluid coolers and evaporative condensers are studied in detail to perform a comprehensive design and rating analysis. The mathematical models are validated using experimental as well as numerical data reported in the literature. These models are integrated with the fouling model presented in an earlier paper, using the experimental data on tube fouling. In this paper, we use the fouling model to investigate the risk based thermal performance of these evaporative heat exchangers. It is demonstrated that thermal effectiveness of the evaporative heat exchangers degrades significantly with time indicating that, for a low risk level (pZ0.01), there is about 66.7% decrease in effectiveness for the given fouling model. Furthermore, it is noted that there is about 4.7% increase in outlet process fluid temperature of the evaporative fluid cooler. Also, a parametric study is performed to evaluate the effect of elevation and mass flow rate ratio on typical performance parameters such as effectiveness for rating calculations while surface area for design calculations. q 2005 Elsevier Ltd and IIR. All rights reserved. Keywords: Refrigeration; Air conditioning Cooling tower; Evaporative